Intensification of production in organic agriculture: coffee case - Noriega Altamirano, Gerardo; Cárcamo Rico Brenda; Gómez Cruz Manuel Ángel; Schwentesius Rindermann, Rita; Cruz Hernández Sergio; Leyva Baeza Jesús; García de la Rosa Eduardo; López Reyes Ulises Iván; Martínez Hernández Alexander (Revista Mexicana de Ciencias Agrícolas, 2018)
In the coastal region of Oaxaca, in the middle of the basin, is the coffee agroe-cosystem, where in addition to environmental services, coffee production is the basis of the rural economy, vulnerable to disasters associated with tropical storms and cyclones. For example, before Hurricane Paulina occurred from 12-15 quintals ha, 13 years after the meteor the coffee have a cover with 81% shade, 7000 kilos of litter has on the ground and an average yield of only 2.9 qq/ha. Soil leaching has led to soil degradation where the pH is 5.4, the C/N of 11.57 and available phosphorus of 17.68 mg kg. Therefore, in demonstration plots scheme is promoted: the restoration of soil biology, organic matter for soil remineralization incorporate nonmetallic secondary minerals, such as zeolites, dolomite and rock phosphate, is practiced inoculation microorganisms: Azotobacter and mycorrhizae, and the incorporation of compost and foliar fertilization.